Strengthening Reading Culture In Madrasah Through Islamic Literacy Strategies: An Integration Of Qur’anic Values - Kurniasih, Siti Dewi; Rodliyah, St.; Turmudi, Imam (Fikroh: Jurnal Pemikiran dan Pendidikan Islam, 2025)
The reading culture in madrasah faces persistent challenges, as students show strong engagement with Qur’anic and religious texts but limited interest in general reading, further weakened by digital distractions. This study addresses the problem by examining how Qur’an-based Islamic literacy strategies can foster a more balanced and sustainable reading culture. Using a qualitative phenomenological design, research was conducted at MTs Miftahul Ulum, Denpasar, Bali, from May to June 2025. Data were collected through classroom observations, semi-structured interviews with teachers and students, and analysis of literacy documents. Triangulation and member checking were employed to ensure validity, while data were analyzed thematically.The findings highlight three main insights. First, reading culture in madrasah remains fragmented, dominated by religious texts with limited exposure to literature, history, or science. Second, Qur’anic values such as Iqra’ (divine command to read) and tadabbur (reflective engaement) provide powerful spiritual motivation and cultivate deeper, critical reading practices. Third, an integrative literacy framework emerges, combining Qur’anic recitation with thematic readings of supplementary texts, which strengthens both spiritual and intellectual engagement. This study contributes theoretically by embedding Islamic perspectives into literacy discourse, challenging secular models that neglect spiritual dimensions. Practically, it offers madrasah educators a framework to integrate Qur’anic values with general reading, creating strategies to develop a holistic, meaningful, and enduring reading culture.